2022
DOI: 10.1093/ijnp/pyac028
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Unique Effects of Long-Term Administration of Methylphenidate and Atomoxetine on Degree Centrality in Medication-Naïve Children With Attention-Deficit/Hyperactive Disorder

Abstract: Background Although methylphenidate (MPH) and atomoxetine (ATX) can improve clinical symptoms and functional impairments in attention deficit/hyperactive disorder (ADHD), the underlying psychopharmacological mechanism have not been clearly elucidated. Therefore, we aimed to explore the shared and unique neurologic basis of these two medications in alleviating the clinical symptoms and functional impairments observed in ADHD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…A recent study (120) suggests that inadequate neuromodulation of prefrontal-cerebellar circuits may underlie cognitive deficits in psychiatric disorders (including schizophrenia, bipolar disorder, and ADHD). In addition, studies (121) showed that both MPH and ATX can restore abnormal brain function in ADHD, mainly involving fronto-cingulo-parieto-cerebellum circuit. In conclusion, the brain changes of patients with ADHD may not be influenced by a single brain region but by multi-channel connections or there may be a certain brain region that is the most critical, which needs to be further studied by other methods such as brain structural network covariation and functional connectivity in the future.…”
Section: Figurementioning
confidence: 99%
“…A recent study (120) suggests that inadequate neuromodulation of prefrontal-cerebellar circuits may underlie cognitive deficits in psychiatric disorders (including schizophrenia, bipolar disorder, and ADHD). In addition, studies (121) showed that both MPH and ATX can restore abnormal brain function in ADHD, mainly involving fronto-cingulo-parieto-cerebellum circuit. In conclusion, the brain changes of patients with ADHD may not be influenced by a single brain region but by multi-channel connections or there may be a certain brain region that is the most critical, which needs to be further studied by other methods such as brain structural network covariation and functional connectivity in the future.…”
Section: Figurementioning
confidence: 99%
“…Specifically, both of the drugs have a moderating effect on the DM and cerebellum. DM serves as a core neuropathological mechanism of attention deficit behavior and cerebellar degree centrality was significantly associated with learning function performance 67 , 68 . Therefore, differential DM and cerebellar connectivity patterns between the two biotypes may influence drug responsiveness, consequently leading to varying symptom improvement outcomes, including inattention, total, and learning problem scores.…”
Section: Discussionmentioning
confidence: 99%